Motor skills - Virginia Commonwealth University; Virginia Association for Retarded Citizen, Inc.; Central Virginia Educational Television (Columbus, Ohio : Charles E. Merrill Pub. Co., 1976)
Concentrates on both gross and fine motor skills and ways of working with the developmentally disabled child to facilitate development in these area.
Keywords: Handicapped children -- Education; Developmentally disabled children -- Care; Motor ability in children